Pengaruh Layanan Perpustakaan Terhadap Kepuasan Pemustaka di Perpustakaan SMA Negeri 2 Padang Provinsi Sumatera Barat - Fitriya Mustika; Marlini Marlini (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2020)
This article discusses the effect of library services on user satisfaction. Some library services found in SMA Negeri 2 Padang include: (1) Circulation Services, (2) Reference Services, (3) Information Retrieval Services, (4) Reading Room Services. Each service applies an open service system (Open Access). The open service system in the library of SMA Negeri 2 Padang has strengths and weaknesses. These strengths and weaknesses are influenced by the usefulness of the existing collection in the library. The influence of library services at the Public High School 2 Padang on the satisfaction of the visitors, among others: guiding users in the development of talents, interests and arts owned by the visitors. Library services provided by SMA Negeri 2 Padang that affect the development of talent, interests, and the art of the library, such as: the library provides a special place to display the works of art of the students or the library.